Developing an instrument to self‐evaluate the Discharge Planning of Ward Nurses. Issue 1 (21st September 2015) - Sakai, Shima; Yamamoto‐Mitani, Noriko; Takai, Yukari; Fukahori, Hiroki; Ogata, Yasuko
Abstract: Aims: To develop the Discharge Planning of Ward Nurses (DPWN), a Japanese self‐evaluation instrument for ward nurses' discharge planning practices. Design: Cross‐sectional survey. Methods: Participants were 624 ward nurses from six hospitals in Japan with a discharge planning department. Items about discharge planning practices were collected from literature and interviews with nurses and researchers. Construct validity, concurrent validity, internal consistency and test–retest reliability were tested. Results: Initially, 55 items were collected. Examination of the floor effect, item‐total, good–poor analyses and exploratory factor analysis yielded a four‐factor model with 24 items ('teaching home‐care skills with community/hospital professionals, ' 'identifying clients' potential needs early in the discharge process, ' 'introducing social resources' and 'identifying client/family wishes and building consensus for discharge'). The four‐factor structure was supported by confirmatory factor analysis. The DPWN correlated with scales ascertaining similar concepts, supporting concurrent validity. Internal consistency and test–retest reliability were generally satisfactory.